Design of Operational Management Information Systems for Route Licenses at the Ternate City Transportation Agency based on Android - Muhammad Ridha Albaar; Akil Thalib; M Kasyif Gufran Umar (Jurnal Ilmiah ILKOMINFO - Ilmu Komputer & Informatika, 2020)
Abstract: The use of information technology in terms of providing data to support the decision-making process has made information systems an essential resource. Ternate City Transportation Agency as a Transportation Agency whose job is to process public transport data, requires an accurate and accurate information system. This study discusses data processing on route permits that are integrated with an android-based database. This research uses Research and Development research procedures. The purpose of this research is to create an information system to process land transportation route permit data and simplify the process of route permit services at the Ternate City Transportation Office so that in submitting the requirements for route permits, it can be accessed via the internetKeywords: Information Systems, Operations, Route Licenses, Android